Medium term survival in patients over ninety years-old undergoing pacemaker implantation. (3rd October 2022) - Zecchin, M; Trevisan, B; Bessi, R; Baggio, C; Salvatore, L; Cappelletto, C; Gregorio, C; Bianco, E; Carriere, C; Longaro, F; Zorzin-Fantasia, A; Saitta, M; et al.
Abstract: Background: According to the Italian National Statistical Institute, the 12-month probability of survival in the general population between 90 and 94 years-old is 26%. Pacemaker (PM) implantation is often an urgent and necessary intervention, but in these patients the benefit in terms of quality and duration of life is unclear. Purpose: To analyze characteristics, outcome and factors associated with survival in patients who had turned 90 at the time of PM implant. Methods: All the PM implants performed in patients ≥90 from 1/1/2019 to 12/31/2020 were analyzed. Clinical parameters, device characteristics and follow-up data were extrapolated from the SuitEstensa Ebit reporting system; the exitus was verified by analyzing data from the Regional Health System. Results: During the study interval, among the 554 patients undergoing PM implantation in our Center, 69 (12%) were ≥90 years-old (mean age 92±2 years, 46% male; complete/advanced AV block in 76%). Twenty-six (38%) patients had history of atrial fibrillation and 19 (28%) ischemic heart disease. A cardiological co-morbidity (excluding AF) was present in 23 patients (33%). Oncological, pneumological and neurological comorbidities were present in 12 (18%), 19 (28%) and 32 (46%) respectively. Renal impairment was present in 25 patients (36%). In 47 patients (68%) there were at least 2 co-morbidities. After implantation (single-chamber in 36, dual-chamber in 25 and VDD single-lead dual-chamber in 8 patients) complications occurred in 3 patients (2 pneumothorax and 1 lead dislodgment). Remote monitoring was activated in 57 patients (83%). Within August 31st 2021 (mean follow-up 288±193 days) 24 patients died (35%, 219±241 days after implant). Five patients (19% of patients implanted in 2019) died within 12 months. No patients died for device malfunction. Three patients died because of COVID-19 pneumonia. Renal dysfunction (Hazard Ratio-HR 8.05, p=0.002) and the presence of 2 or more co-morbidities (HR 6.03; p=0.015) were associated with a higher risk of death at univariate analysis; other significant variables were diabetes (HR 2.34; p=0.038), left ventricular ejection fraction (LVEF) (HR 0.70 for 5% variation; p=0.005), walking impairment (HR 2.99, p=0.006), the presence of oncological (HR 2.21; p=0.003), pneumological (HR 2.55; p=0.024) and neurological (HR 1.90, p=0.007) comorbidities. At multivariable analysis the only significant parameter associated with survival was LVEF (0.76 for 5% difference; p=0.043) Conclusions: At our Center, patients ≥90 years-old undergo PM implantation mainly for advanced AVB. The good survival in the medium term, even better than expected in the general population, does not justify a too conservative attitude especially, but exclusively, in patients with less comorbidities. Funding Acknowledgement: Type of funding sources: None.